The First Android Client Application for the iLab Shared Architecture - Deaky, Bogdan-Alexandru; Garbi Zutin, Danilo; Bailey, Philip (International Journal of Online and Biomedical Engineering (iJOE), 2012)
This paper presents the first Android client application developed for online laboratories based on the iLab Shared Architecture. An important challenge was to properly connect to the ISA Service Broker, because its current version was developed with browser-based client applications in mind. The application was successfully tested on a few real-world mobile devices and the experience gained represents the basis for future changes in the Service Broker and for future teleengineering applications that involve Android.